Literasi Ekonomi Syariah pada Kelompok Tani Desa Kaana Kecamatan Enggano - Gunawan Amirudin; Romi Adetio Setiawan; Evan Stiawan (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim of sharia economic literacy in the Kaana village farmer group, Regano subdistrict is to educate members of the Agree Farmer group in order to increase understanding and knowledge in understanding Islamic economics in life in the Kaana village farmer group, Regano subdistrict, North Bengkulu district, Bengkulu province. Before the assistance was implemented, many of the members of the farmer groups still did not understand sharia economics. Then at the end of the service assistance, the farmer group members agreed that the farmers of Kaana village, Ogano subdistrict, North Bengkulu district were able to know/understand the guidelines used in buying and selling activities following the sharia economic system which is based on the Al-Quran and Hadith.